Fracture envelope estimation of a structural adhesive by dedicated fracture tests - Nunes, F.A.A. (2020)
Cohesive zone modelling (CZM) is widespread for the strength analysis of bonded joints. The fracture toughness (GC) is required to use CZM. A scarcely studied mixed-mode test is the Asymmetric Tapered Double-Cantilever Beam (ATDCB), which merges a Tapered Double-Cantilever Beam (TDCB) adherend with a Double-Cantilever Beam (DCB) adherend. This work addresses the ATDCB test to estimate the fracture envelope of a structural adhesive. TDCB and End-Notched Flexure (ENF) tests were also performed to acquire the tensile (GIC) and shear fracture toughness (GIIC), respectively. Numerically, mixed-mode CZM laws were constructed based on the obtained data, and the results were compared with experiments, to validate the CZM laws and the mixed mode propagation criterion. As a result, the best damage propagation criterion for mixed mode was estimated and validated.